Большой баклан (Phalacrocorax carbo L.) как потенциальный источник распространения гельминтозов рыб, охотничье-промысловых и домашних птиц - Корнюшин, В.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Data on helminth fauna of the Cormorant in the Ukraine are summarized. In total 26 helminth species are noted, including 2 species of cestodes, 16 species of trematodes and 8 species of nematodes. The circle of intermediate, supplementary and definitive hosts of these helminthes is analyzed. It is shown that most of them develop with the participation of fishes. On this basis potential role of the Cormorant in helminthosis spreading, dangerous for game-fish, pisciculture, game-birds, fowls, dogs, cats and also for people was estimated.